Fixation Differences in Spatial Visual Perception During Multi-sensory Stimulation - Kim, Jihoon; Kim, Ju Yeon (Frontiers in Psychology, 2020)
The mood and atmosphere of a service setting are essential factors in the way customers evaluate their shopping experience in a retail store environment. Scholars have shown that background music has a strong effect on consumer behavior. Retailers design novel environments in which appropriate music can elevate the shopping experience. While previous findings highlight the effects of background music on consumer behavior, the extent to which recognition of store atmosphere varies with genre of background music in sales spaces is unknown. We conducted an eye-tracking experiment to evaluate the effect of background music on the perceived atmosphere of a service setting. We used a 2 (music genre: jazz song with slow tempo vs. dance song with fast tempo) × 1 (visual stimuli: image of coffee shop) within-subjects design to test the effect of music genre on visual perception of a physical environment. Results show that the fixation values during the slow tempo music were at least two times higher than the fixation values during the fast tempo music and that the blink values during the fast tempo music were at least two times higher than the blink values during the slow tempo music. Notably, initial and maximum concentration differed by music type. Our findings also indicate that differences in scan paths and locations between the slow tempo music and the fast tempo music changed over time. However, average fixation values were not significantly different between the two music types.